Evaluating Communication Policies in Grant Management for Islamic Institutions: A Case Study of BKAD North Sumatra - Muhammad Rahmadani Lubis; Hasan Sazali; Hasnun Jauhari Ritonga (INJECT (Interdisciplinary Journal of Communication), 2025)
This study aims to analyze the communication policies of the Regional Finance and Asset Agency (BKAD) of North Sumatra Province in managing grants for Islamic institutions, including the implementation of good governance principles, the effectiveness of guidance and assistance, as well as the supporting and inhibiting factors in the grant management process. Using a qualitative descriptive method, data were collected through in-depth interviews, observations, and documentation involving BKAD officials and Islamic organizations receiving grants. The findings reveal that although BKAD has established formal regulations through Governor Regulation No. 19/2022, the implementation of communication policies remains suboptimal. Information dissemination is predominantly one-directional, causing gaps in understanding and frequent administrative errors. Guidance and technical assistance are limited, resulting in difficulties for institutions in preparing RAB, SPJ, and financial documentation. Furthermore, the application of good governance principles transparency, accountability, and effectiveness is inconsistent, mainly due to passive information delivery, limited institutional capacity, and insufficient monitoring. Supporting factors include the availability of clear regulations, BKAD's commitment to improving services, and institutions' willingness to learn. However, low administrative literacy, lengthy bureaucracy, limited BKAD human resources, and weak evaluation mechanisms hinder implementation. This study contributes theoretically and practically by highlighting the need for two-way communication, capacity building, and continuous monitoring to strengthen financial governance among Islamic institutions